Methods for evaluating in-duct noise attenuation performance in a muffler design problem - Lee, Jong Kyeom; Oh, Kee Seung; Lee, Jin Woo (Journal of Sound and Vibration, 2020)
In this study, methods for evaluating the noise attenuation performance of a muffler in a muffler design problem are investigated, and a proper evaluation method is suggested for actual noise reduction in a duct when an optimally designed muffler is mounted on a duct. Mathematical expressions of the transmission loss, insertion loss, and level difference for a simple expansion chamber muffler are developed from basic acoustic equations. The effects of the locations of the measurement points, tailpipe length, and impedance at the end of the duct on the noise attenuation performance calculated using the three evaluation methods are discussed. The TL and IL maximization problems formulated using topology optimization are solved for a muffler unit, and the noise attenuation performances of the optimally designed mufflers are compared when mounted on a duct. Another acoustical topology optimization problem, a partition volume minimization problem for a muffler design, is formulated to reduce the in-duct broadband noise, and the noise attenuation performance of the optimal muffler obtained using this formulation is experimentally validated. These research results will contribute to the development of a muffler design method with high accuracy by reducing the discrepancy between the noise attenuation performances of a muffler unit and a muffler mounted on a duct.
Keywords: Evaluation methods; Level difference; Mathematical expressions; Maximization problem; Muffler design; Noise attenuation; Transmission loss; Volume minimization; Insertion loss; Level difference; Muffler design; Noise attenuation performance; Topology optimization; Transmission loss